Ether: the disappearance of violet bell ebook - Kindt, Matt (Ether: The Disappearance of Violet Bell (2019)., 2020)
From New York Times bestselling Mind MGMT creator MATT KINDT and Black Hammer's DAVID RUBÍN comes the third volume of this fantasy adventure that's Sherlock Holmes meets Dr. Seuss. The Faerie King's daughter is missing and only portal jumper Boone Dias can track her down. Jumping from one magical crime scene to another he uncovers a bizarre plot featuring assassin eggs, weird pirates, ice deserts, and more noir absurdities. Collecting issues #1-5 of Ether series III and featuring a sketchbook section with bonus art from Paul Azaceta, Kevin Nowlan, Gabriel Walta, and more.